Analysis of the sulfate permease family in Bursaphelenchus xylophilus in the nematode development and stress adaptation - Li, Haixiang; Wang, Rui; Pu, Na; Yang, Song; Chen, Jie; Hao, Xin (Frontiers in Plant Science, 2025)
IntroductionPine wilt disease (PWD), caused by the pine wood nematode (PWN) Bursaphelenchus xylophilus, poses a significant threat to global pine forests. The sulfate permease (SULP) family is essential for sulfate transport, sulfur assimilation and cellular homeostasis, yet it remains uncharacterized in B. xylophilus. This study aimed to comprehensively identify all members of the SULP family in B. xylophilus and to elucidate their roles in nematode development and stress adaptation.MethodsThrough genomic data analysis, we identified 10 members of the SULP family in B. xylophilus and conducted a comprehensive characterization of their physicochemical properties, conserved motifs, protein structures, and gene expression profiles across different developmental stages.ResultsThe results revealed Bx-sulps were located on 5 chromosomes of B. xylophilus. Phylogenetic analysis unveiled both conserved and divergent evolutionary patterns of these proteins compared to counterparts in other nematodes. Expression analysis demonstrated upregulation of Bx-sulps during the dauer third-instar larva (D3) stage, suggesting their involvement in stress response and diapause. Moreover, certain Bx-sulps exhibited high expression levels in adult stages, indicating a potential role in reproductive processes.DiscussionThe study presents the first comprehensive examination of BxSULP family, shed light on its significance in nematode development and stress adaptation. These findings provide the groundwork for further functional investigations and may aid in the development of targeted strategies for managing PWD.